2007
DOI: 10.1097/00005082-200701000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Applying Research Evidence to Optimize Telehomecare

Abstract: Telemedicine is the use of technology to provide healthcare over a distance. Telehomecare, a form of telemedicine based in the patient's home, is a communication and clinical information system that enables the interaction of voice, video, and health-related data using ordinary telephone lines. Most home care agencies are adopting telehomecare to assist with the care of the growing population of chronically ill adults. This article presents a summary and critique of the published empirical evidence about the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
89
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(89 citation statements)
references
References 21 publications
0
89
0
Order By: Relevance
“…[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] These showed that evidence of effectiveness was stronger for some conditions (e.g. heart failure) than for others (e.g.…”
Section: Lack Of Evidence About Effectiveness and Cost-effectivenessmentioning
confidence: 99%
See 3 more Smart Citations
“…[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] These showed that evidence of effectiveness was stronger for some conditions (e.g. heart failure) than for others (e.g.…”
Section: Lack Of Evidence About Effectiveness and Cost-effectivenessmentioning
confidence: 99%
“…16,17,[69][70][71]73,77 Two reviews reported improved educational outcomes 11,73 and seven reported significant positive behavioural change, 11,17,20,68,71,73,75 particularly improved self-monitoring or management in patients with diabetes 17 and better treatment adherence. 17,20,68 There were few firm conclusions about the impact of telehealth on quality of life, although one meta-analysis reported improvements associated with computer-mediated support groups. 75 The three reviews which suggested that telehealth improved social support 11,73,75 were countered by three that reported inconsistent or insufficient evidence.…”
Section: Specific Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…58,73 While the many studies conducted show the potential cost savings due to telehealth and remote monitoring, both in the US and in other countries, the fact that most of these studies still involve small sample sizes with diverse types and doses for telehomecare intervention and for select chronic illnesses, such as heart failure and COPD presents a challenge to the revenue model. 27,[74][75][76][77][78] Also, other studies argue that the outcome of telemedicine in these areas is not conclusive due to definition and measurement issues. 79,80 A 1992 study by the Arthur D. Little Consulting Company which estimated then, that telemedicine would have resulted in savings of $36 billion annually, was perhaps the first, and one of the few, comprehensive studies that tried to estimate the potential savings from telemedicine.…”
Section: Revenue Modelmentioning
confidence: 99%